O conceito de desenvolvimento segundo Hegel: a progressão da consciência - Malinski, Tania Alexandra (Universidade Federal de São Carlos, 2012)
The present thesis defends that Hegel´s dialectic can be understood as a process of development, both from the standpoint of pure reason and from a perspective based on historical and political factors. The dialectic of the concept is a development of the consciousness of being with relation to an object so as to comprehend the universal content of the object. The preservation of what is in opposition in the dialectical synthesis is the nucleus of the idea of development and what gives it a positive, constructive and directional character as philosophical and historical process. From a strictly rational point of view, development is the progression of consciousness. From a historical perspective, development is the progressive manifestation of spirit, or Geist. Both means of development consolidate themselves with the enunciation of the concept, which envelops an internal and subjective determination as well as a normative element. The philosophical law contained in the concept reveals its intrinsic value and its comprehension becomes a constitutive part of being. The determination in terms of rule of law and moral values is the absolute determination towards which is driven the national spirit.
Keywords: Filosofia; Desenvolvimento; Consciência; Conceitos; Dialética; Espírito; Absoluto; Ação; Constituição; Desigualdade; Geist; Essência; Estrutura; Força; Humanização; Idealismo; Identidade; Liberdade; Movimento; Motivo; Negativo; Objeto; Oposição; Potência; Ser; Ser-em-si; Ser-para-si; Síntese; Substância; Sujeito; Universal; Absolute; Action; Consciousness; Constitution; Development; Inequality; Dialectics; Spirit; Geist; Essence; Structure; Force; Humanization; Idealism; Identity; Liberty; Movement; Motive; Negation; Object; Opposition; Potentiality; Being; Being-in-itself; Being-for-itself; Synthesis; Substance; Subject; Universal; CIENCIAS HUMANAS::FILOSOFIA